2019
DOI: 10.1093/jscr/rjz102
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous gastric and colonic erosions from gastric band and its tubing in the setting of recurrent intra-abdominal infection

Abstract: Chronic abdominal pain is often a diagnostic dilemma. We present a 59-year-old female with chronic generalized colicky abdominal and altered bowel habits. She was investigated with colonoscopy and CT abdomen. Patient has a history of recurrent diverticulitis and insertion laparoscopic adjustable gastric band. The colonoscopy revealed a tubular foreign body and diverticular disease. The tubular structure was confirmed to be gastric band tubing on CT abdomen, also showing simultaneous gastric and colonic erosion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Erosion into the colon is less commonly observed, and the simultaneous erosion of the gastric band apparatus into both the stomach and the transverse colon is extremely uncommon. To our knowledge, there are no original research studies that investigate the prevalence of gastric band erosion into both the stomach and the colon simultaneously, and the pathology has been described in only a few case reports [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erosion into the colon is less commonly observed, and the simultaneous erosion of the gastric band apparatus into both the stomach and the transverse colon is extremely uncommon. To our knowledge, there are no original research studies that investigate the prevalence of gastric band erosion into both the stomach and the colon simultaneously, and the pathology has been described in only a few case reports [2][3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…There are two primary proposed etiologies for erosion at the site of the gastric band: (1) elevated pressure caused by overfilling of the band or excessive food boluses and (2) rejection reaction against the silicon of the gastric band with circumferential fibrosis [8]. It has further been previously proposed that repeated episodes of intra-abdominal infection may cause subacute infection of gastric band and tubing, which, in the setting of friable colonic tissue, may predispose to erosion [2]. Furthermore, it has been suggested that the most likely mechanism leading to gastric band connecting tubing erosion is through bacterial colonization of the tubing due to port infection [9].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, patients lost weight but soon adapted to eat less and ate higher calory content [16,17]. But, unfortunately, the band itself was also a source of many other problems like infections [18], migration [19], erosion [20] and even, on rare occasions to gastric perforation [21]. As a result, conversion to other bariatric surgical procedures has not been uncommon [22].…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…A high clinical index of suspicion is necessary to diagnose BE, as most patients are asymptomatic [6]. Previous studies have reported several cases of gastric BE in the gastrointestinal (GI) tract [6][7][8][9][10][11]. Conversely, the formation of a GI fistula is an extremely rare complication that can occur simultaneously with gastric BE [12,13].…”
Section: Introductionmentioning
confidence: 99%